En route to New York: diasporic networks and the reconfiguration of female entrepreneurship in Senegal. Issue 4 (2nd April 2016) - Lo, Marieme S.
Abstract : This article examines the influence of migration and transnational social networks on female entrepreneurship. It interrogates shifting patterns of market development, juxtaposed to the lure of new economic opportunities for women entrepreneurs located at the periphery, Senegal. I critically analyse how a distinct and classed category of Senegalese women entrepreneurs navigates international spaces and legal restrictions in attempts to launch profitable economic ventures in metropolitan centres such as New York City and negotiate new forms of representation and agency in contentious socio-economic spaces. By interrogating the complex interplay between women entrepreneurs and diasporic communities, I weave an often-missing gender perspective into the analysis of the emergence of female transnational entrepreneurship and diasporic social networks. This article demonstrates that diasporic social networks, transnational markets and spatial interconnections, while contributing to market revitalisation and expansion, are nonetheless fraught with tension. Diasporic social networks embody paradoxical positions. They represent an enabling economic transactional space, while embodying an informal social space that nonetheless remains sites of power struggles deeply embedded in gendered, sociocultural and economic dynamics that transfer from local to transnational contexts.